ANALISIS STRATEGI MIX MARKETING DI TK KHALIFAH 1 BANDA ACEH - Novita Safitri; Rani Puspa Juwita; Zikra Hayati (Al Athfal : Jurnal Kajian Perkembangan Anak dan Manajemen Pendidikan Usia Dini, 2023)
The mix marketing strategy is an educational service marketing strategy consisting of product, price, place, promotion, people, physical evidence and process which aims to win the education market. From the observation results, Kindergarten Khalifah 1 Banda Aceh is a Kindergarten with quality education facilities and services and has been accredited A. Therefore the purpose of this study is to analyze the mix marketing strategy in Kindergarten Khalifah 1 Banda Aceh and the obstacles to its implementation as an effort to win the market early childhood education programs. This research approach is qualitative with descriptive qualitative type, data collection techniques (observation, documentation, and interviews), as for data analysis (data reduction, data display, and drawing verification conclusions). The results of the study show that the superior products offered are tauhid-based learning and entrepreneurship. Prices for kindergarten class Rp. 7,250,000, playgroup Rp. 6,450,000, and daycare Rp. 3,050,000/per year. Place/strategic location/easy to reach. Promotion through direct contact and social media. People (HR) consists of 29 people. Physical Evident, namely 11 class learning classes and several other facilities. The learning process uses K-13, the central learning model. The obstacle to its application to the price element is that some parents are not punctual in making payment for education fees, and in the learning process, sometimes there are some children who do not pay attention to the lesson, so that the learning objectives cannot be achieved properly. Keywords: Analysis, Strategy, Marketing Mix